Copyright Versus Open Access On the Organisation and International Political Economy of Access to Scientific Knowledge - Scheufen, Marc.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book addresses the recent debate about copyright law and its impact on the distribution of scientific knowledge from an economic perspective. The focus is on the question whether a copyright regime or an open access regime is better suited to the norms and organizational structure in a purely global science community. The book undertakes a thorough economic analysis of the academic journal market and showcases consequences of a regime change. It also takes account of the Digital Divide debate, reflecting issues in developing countries. Finally, a comprehensive analysis of legal action in the light of international Intellectual Property (IP) agreements offers prospects on the future of academic publishing.
Introduction -- Some Fundamental Economics -- Academic Journal Publishing and the Open Access Movement -- On the Access Principle in Science: A Law & Economics Analysis -- The Future of Academic Publishing -- Conclusions and Further Research -- Appendix.
Keywords: Economics; Industrial organization (Economic theory).; Commercial law; Economics/Management Science; Law and Economics; International IT and Media Law, Intellectual Property Law; Emerging Markets/Globalization.; Industrial Organization